2020
DOI: 10.1016/j.ajhg.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

NCKAP1 Disruptive Variants Lead to a Neurodevelopmental Disorder with Core Features of Autism

Abstract: NCKAP1/NAP1 regulates neuronal cytoskeletal dynamics and is essential for neuronal differentiation in the developing brain. Deleterious variants in NCKAP1 have been identified in individuals with autism spectrum disorder (ASD) and intellectual disability; however, its clinical significance remains unclear. To determine its significance, we assemble genotype and phenotype data for 21 affected individuals from 20 unrelated families with predicted deleterious variants in NCKAP1. This includes 16 individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Candidate genes which have been the focus of ASD are: CACNAIC , GABAA receptor subunit , FOXP2 , HOXA1 , HOXB1 , HTR2A , MTHFR , RELN , RAY1/ST7 , IMMP2L , SLC6A4 , OXTR , UBE3A and WNT-2 [ 26 , 27 , 28 , 29 , 30 , 31 ]. More recently, a role for de novo deleterious NCKAP1 variants was reported in neurodevelopmental delay/autism, as variants can affect the neuronal migration in early cortical development [ 32 ]. POU3F2 , was identified as ASD risk gene, and it is a key transcription factor involved in neuronal differentiation, whose downstream target genes are strongly enriched for known ASD genes and mutations [ 33 ].…”
Section: Genetics Studiesmentioning
confidence: 99%
“…Candidate genes which have been the focus of ASD are: CACNAIC , GABAA receptor subunit , FOXP2 , HOXA1 , HOXB1 , HTR2A , MTHFR , RELN , RAY1/ST7 , IMMP2L , SLC6A4 , OXTR , UBE3A and WNT-2 [ 26 , 27 , 28 , 29 , 30 , 31 ]. More recently, a role for de novo deleterious NCKAP1 variants was reported in neurodevelopmental delay/autism, as variants can affect the neuronal migration in early cortical development [ 32 ]. POU3F2 , was identified as ASD risk gene, and it is a key transcription factor involved in neuronal differentiation, whose downstream target genes are strongly enriched for known ASD genes and mutations [ 33 ].…”
Section: Genetics Studiesmentioning
confidence: 99%
“…A possible association between NCKAP1 (HGNC:7666) and intellectual disability has already been proposed in 2017, while subsequent studies have further supplemented evidence for this gene–disease association through the collection of larger cohorts [ 9 , 10 , 11 , 12 ]. However, until now, there has been no OMIM association between NCKAP1 and the phenotypes of intellectual disability and autism, as proposed by the abovementioned studies.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling by NTRK1 (TRKA) [55], cardiac conduction [56], signaling by GPCR [57], immune system [58], cytokine signaling in immune system [59], interferon signaling [60] and toll-like receptor cascades [61] were responsible for development of PD. Recent studies have shown that EGR2 [62], WNT1 [63], ARC (activity regulated cytoskeleton associated protein) [64], CHRNA7 [65], SEZ6L2 [66], IL1RAPL2 [67], PER2 [68], PCDH19 [69], CNTNAP2 [70], SLC12A5 [71], CDK5 [72], ACTL6B [73], GABRD (gamma-aminobutyric acid type A receptor subunit delta) [74], CACNA1G [75], HTR2C [76], STX1A [77], ATP1A3 [78], RIMS3 [79], CNTNAP2 [80], CDH8 [81], SCAMP5 [82], SYNGR1 [83], ARHGEF9 [84], DLG3 [85], RBP4 [86], IL9 [87], S100A9 [88], HGF (hepatocyte growth factor) [89], C3 [90], FKBP5 [91], GABRE (gamma-aminobutyric acid type A receptor subunit epsilon) [92], NCKAP1L [93], PIK3CG [94], ITGB3 [95], ANXA1 [96], SYNE2 [97] and DBI (diazepam binding inhibitor, acyl-CoA binding protein) [98] were closely involved with the occurrence, development, and prognosis of autism spectrum disorder. EGR2 [99], ADCYAP1 [100], CHRNA7 [101], NRN1 [102], ETV5 [103], STXBP1 [104], CAMKK2 [105], VAMP2 [106], SYNGR1 [107], NOD2 [108], TLR2 [109], BRCA2 [110] and LEF1 [111] were previously reported to be critical for the development of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%